Determination of volatile constituents of Thai fragrant orchids by gas chromatography-mass spectrometry with solid-phase microextraction - Jakaphun Julsrigival (2018)
Volatile constituents of four Thai fragrant orchid species, Rhynchostylis gigantea Ridl., Rhynchostylis gigantea var. harrisonianum Holtt., Vanda coerulea and Dendrobium parishii Rchb. f., were examined by Gas Chromatography-Mass Spectrometry (GC-MS). Three parts of each plant sample (the flowers, leaves and roots) were analyzed for volatile compounds using the Headspace - Solid-Phase Microextraction method (HS-SPME). Alcohols, aldehydes, alkanes, esters, ethers, ketones, monoterpenes and sesquiterpenes were identified quantitatively from the volatile compounds isolated from the flower parts. The aromatic compounds isolated differed among the orchid species. The major aromatic compounds of the flowers of R. gigantea, R. gigantea var. harrisonianum, V. coerulea and D. parishii. were nerol (25.42%), 2,3-dihydrofarnesol (34.30%), nonanal (34.69%) and 2-pentadecanone (43.47%), respectively.